De pé, os muros seguem - Souza, Maurin (2015)
Based on the concepts of contemporary and literary engagement, I aim with this thesis analyze the short story "The Wall" by Jean-Paul Sartre, and the novels In slow motion, by Renato Tapajós, and Installation of fear, by Rui Zink. The historical moments portrayed in these narratives are the Spanish Civil War, World War II - albeit indirectly, the Brazilian Military Dictatorship and the 2000s (these with small rescues to episodes occurred in the twentieth century). It is my intention also check what feelings that permeate the Man of decades from 1930 to 1980 (anxiety, fear, loneliness, courage, indifference, anger) and if they, today, linger, given the way in which contemporary presents itself and as a reference, therefore, the work of Rui Zink. As I consider essential to be attentive and, more importantly, involve myself with the society for which I am responsible, I instigate discussions about the role of written word as a compromise and I direct it to authors who I understand as engaged and, therefore, I chosed to complete my dissertation.